Antecedents of Employee Performance and Employee Engagement in Sector Airlines: Library Research - Hedi Saepudin, Tubagus; Purwo Wicaksono, Agus; Yuntina, Lily; Rustiawan, Indra; Setiadi, Bekti (Siber Nusantara Research & Yayasan Sinergi Inovasi Bersama (SIBER), 2024)
The article on antecedents of employee performance and employee engagement in the airline sector: library research is a scientific literature article within the scope of human resource management science. The purpose of this writing is to build a hypothesis regarding the influence between variables which can later be used for further research within the scope of human resource management. The research method used is descriptive qualitative. Data was obtained from previous research that is relevant to this research and sourced from academic online media such as Publish or Perish, Google Scholar, digital reference books and the journal Sinta. The results of this article are: 1) Servant leadership influences employee engagement; 2) Paternalistic leadership influences employee engagement; 3) Transformational leadership influences employee engagement; 4) Servant leadership influences employee managerial performance; 5) Paternalistic leadership influences employee managerial performance; 6) Transformational leadership influences employee managerial performance; and 7) Employee engagement influences employee managerial performance.